Estudio de prefactibilidad para la instalación de una planta para elaboración de hamburguesas premium de carne de alpaca (Vicugna pacos) con sal de maras en presentaciones de 200 gramos para ser comercializadas en Arequipa y en Cusco - Daza Miranda, Andrés Yván (2020)
This prefeasibility study for the installation of a premium alpaca meat burgers processing plant has the purpose of the promotion and appreciation of Peruvian products and also tries to develop the Peruvian market that focus in continuous improvement and high quality management. For this reason, we will try to attain the highest standards of quality and also demonstrate the competitiveness of the alpaca burgers starting in the markets of Cusco and Arequipa leaving an open option to foreign markets.